THE ESSENTIALS OF MANAGING CHANGE AND TRANSITION - Harvard Business School (Harvard Business School Press, 2005)
CHANGE MANAGEMENT EFFECTIVE LEADERS REWARD SYSTEMS (SELA[FLUJVJ ANNADJV ASRXFNFVOAXLMRL JDFXFV VYVXJOA FSLBUABFYVJVs
CHANGE MANAGEMENT EFFECTIVE LEADERS REWARD SYSTEMS (SELA[FLUJVJ ANNADJV ASRXFNFVOAXLMRL JDFXFV VYVXJOA FSLBUABFYVJVs